The Transfer Teknologi Budidaya Anggrek Hasil Kultur Jaringan Terhadap Para Santri Pondok Pesantren Nurul Islam Jember: Pelatihan aklimatisasi bibit anggrek hasil kultur jaringan - Mohammad Nur Khozin; Dwi Erwin Kusbianto; Sigit Soeparjono; Muhammad Dima Say Mona; Didik Pudji Restanto (Universitas Mataram, 2022)
The Nurul Islam Islamic Boarding School Antirogo Jember is one of the modern Islamic boarding schools where in addition to teaching about religious sciences, science and technology lessons are mandatory lessons for students at Islamic boarding schools. The transfer of technology for orchid cultivation resulting from tissue culture aims to increase the insight, knowledge and skills of the students in the fields of science and technology so that it has a positive impact on the preservation of orchids, the beauty of the environment, and adds economic value. Tissue culture techniques are very effective in the propagation of orchids. The results of tissue culture are usually found in the form of seeds. In order to live and grow outside the bottle, the orchid seeds must be removed. But there is a special treatment so that the seeds can become seeds that are able to grow outside the bottle. This technique is an acclimatization technique. For the students, of course, the skill to acclimatize orchids is very useful. so that it is hoped that it can add new knowledge, insight, and skills for the students, starting from selecting seeds, preparing planting media, transplanting seeds from bottles to pots, and caring for seedlings. Keywords: